Development and optimization of social skills in children of preschool age who come from single-parent families vs. biparental. - Sandu, Mihaela Luminița; Călin, Mariana Floricica; Trandafir, Georgiana (Technium Social Sciences Journal, 2022)
The research started from the idea that preschool age is a very important moment in children's lives, they learn to relate to the people around them and solve various social situations that they face every day. Preschool age is a time of discovery, of socialization, of shaping self-awareness. Another objective from which we started is that more and more families are dividing and most of the time children grow up with one parent. The actions of the parent guide the child's social development and provide him with the framework for the formation of self-confidence, therefore the parent who remains in the single-parent family must be a good example for his child for a good development because the child observes and imitates the behavior of the parent, he being the closest human model.